2019
DOI: 10.1101/761429
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A single-cell and single-nucleus RNA-seq toolbox for fresh and frozen human tumors

Abstract: AbstractSingle cell genomics is essential to chart the complex tumor ecosystem. While single cell RNA-Seq (scRNA-Seq) profiles RNA from cells dissociated from fresh tumor tissues, single nucleus RNA-Seq (snRNA-Seq) is needed to profile frozen or hard-to-dissociate tumors. Each strategy requires modifications to fit the unique characteristics of different tissue and tumor types, posing a barrier to adoption. Here, we developed a systematic toolbox for profiling fresh and frozen … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
176
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(186 citation statements)
references
References 31 publications
10
176
0
Order By: Relevance
“…Frozen kidney biopsy specimens or frozen samples of macroscopically normal cortex from tumor nephrectomies (distant from the tumor site), were obtained after appropriate patient (discarded tissue) consent and in accordance with Partners Healthcare IRB and institutional guidelines. One of two protocols (utilizing either nuclei EZ lysis buffer (Sigma-Aldrich, St. Louis, USA) or a salt Tris-based buffer (27,28)) was used to isolate nuclei from these; in the case of kidney biopsy tissue, the surrounding OCT embedding medium was first removed using PBS. 8,000 or 10,000 single nuclei were loaded into each channel of the Chromium single cell 3' chip, according to use of the v2 or v3 kit respectively (10x Genomics, Pleasanton, USA).…”
Section: Single Nucleus Isolation From Human Kidney Tissuementioning
confidence: 99%
“…Frozen kidney biopsy specimens or frozen samples of macroscopically normal cortex from tumor nephrectomies (distant from the tumor site), were obtained after appropriate patient (discarded tissue) consent and in accordance with Partners Healthcare IRB and institutional guidelines. One of two protocols (utilizing either nuclei EZ lysis buffer (Sigma-Aldrich, St. Louis, USA) or a salt Tris-based buffer (27,28)) was used to isolate nuclei from these; in the case of kidney biopsy tissue, the surrounding OCT embedding medium was first removed using PBS. 8,000 or 10,000 single nuclei were loaded into each channel of the Chromium single cell 3' chip, according to use of the v2 or v3 kit respectively (10x Genomics, Pleasanton, USA).…”
Section: Single Nucleus Isolation From Human Kidney Tissuementioning
confidence: 99%
“…Thirdly, it relies on the isolation of intact cells from fresh tissues, which hinders its clinical application on human samples. In this context, single-nucleus RNA-seq has emerged as a complementary approach that relies on the unbiased assessment of nuclei from all cells present in a tissue [20,21,36]. The analysis of the nuclear transcriptome has been proven to be very powerful to study cell type diversity in the mouse and human tissues, including brain [21,[23][24][25][26][27]111]; spinal cord [50]; breast cancer [51]; kidney [29][30][31][32]; lung [28]; heart [33,34]; and a variety of human tumor samples [36].…”
Section: Discussionmentioning
confidence: 99%
“…S1C). This correlation shows that single-nucleus RNA-seq2 is a robust and reliable approach to study transcriptional profiles of individual cells from archived frozen tissues [20,23,25,36,[50][51][52]. The main improvement of our approach relies on the addition of a supplementary lysis buffer compatible with the generation of full-length cDNA and library preparation without the need for additional clean-up steps.…”
Section: Snrna-seq2 Allows Deep and Robust Characterization Of Singlementioning
confidence: 92%
See 1 more Smart Citation
“…While a complex framework such as Cumulus cannot provide an optimal combination of specialized algorithms for each application, it will accelerate research by providing an integrated and fast approach that enables more labs to analyze large-scale single-cell and single-nucleus datasets. In a separate study 49 , we demonstrated Cumulus by analyzing single-cell and single-nucleus RNA-seq data from fresh and frozen tumor from the Human Tumor Atlas Pilot Project (HTAPP). As the community produces data sets at substantially larger scales, we hope that Cumulus will play a key role in the effort to build atlases of complex tissues and organs at higher cellular resolution and leveraging them to understand the human body in health and disease.…”
Section: Hnsw Has a Near Optimal Recall (Supplementarymentioning
confidence: 99%